2022
DOI: 10.1101/2022.12.13.520229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A subcortical origin for rapid, target-oriented corticospinal excitability modulation during visually guided reaching

Abstract: During visually guided reaching, proximal limb muscles can be activated within 80 ms of target appearance. Such 'express' visuomotor responses are temporally aligned with target appearance rather than movement onset, and invariably tuned towards the direction of the visual target regardless of the instructed reach direction. These features prompt the hypothesis that express visuomotor responses are driven by a subcortical pathway. We tested this by measuring the changes in Motor Evoked Potentials (MEPs) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
4
2
0
Order By: Relevance
“…Follow up pairwise comparisons showed that corticospinal excitability at 80 ms was influenced by the location of the target in both pro-( P = 0.005, Figure 7A ) and anti-reach conditions ( P = 0.007, Figure 7B ). This is consistent with the early target-oriented excitability changes observed earlier (Divakar et al, 2022), confirming our finding that the visual information has rapid access to the corticospinal tract as early as 80 ms. In that paper, we saw that the target-related MEP changes at 80 ms were immediately followed by the movement-related changes at 90-100 ms. By contrast, here we saw a significant temporal gap between the early target-related and late movement-related excitability changes.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Follow up pairwise comparisons showed that corticospinal excitability at 80 ms was influenced by the location of the target in both pro-( P = 0.005, Figure 7A ) and anti-reach conditions ( P = 0.007, Figure 7B ). This is consistent with the early target-oriented excitability changes observed earlier (Divakar et al, 2022), confirming our finding that the visual information has rapid access to the corticospinal tract as early as 80 ms. In that paper, we saw that the target-related MEP changes at 80 ms were immediately followed by the movement-related changes at 90-100 ms. By contrast, here we saw a significant temporal gap between the early target-related and late movement-related excitability changes.…”
Section: Resultssupporting
confidence: 93%
“…In experiment two, neither the MEP nor the background EMG was influenced by goal-directed activity in the early stages of reaching ( Figure 7 ). This confirms that the early excitability changes that we reported previously (Divakar et al, 2022) were due at least in part to the express visuomotor response and not due solely to an overlap with the early voluntary response. The results from the two experiments in the current study were also consistent, in that both MEPs and background EMG prior to 140 ms appeared to show an alternating pattern in both pro- and anti-reach conditions, with clear target-oriented MEP modulation at 80 ms ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Reach-related neurons in the dSC display short-latency visual responses (Werner et al, 1997a(Werner et al, , 1997b and correlate with upper limb muscle activity (Werner et al, 1997a;Stuphorn et al, 1999), although the properties of visual responses in reachrelated neurons have not been systematically investigated. Our speculation of a subcortical route initiating visually-guided reaches to a punctate target is consistent with recent stimulation results in humans (Divakar et al, 2022), and parallels a growing appreciation for the role of subcortical pathways in manual following responses to whole-field motion (Saijo et al, 2005) or flashes (Nakajima et al, 2021).…”
Section: Implications Of Our Resultssupporting
confidence: 89%